Revolutionizing Healthcare with AI and Deep Learning Smart Health Monitoring for Early Detection and Enhanced Patient Care - Vinay Kumar Maginam (Journal of Computational Analysis and Applications (JoCAAA), 2025)
The evolution of technology has reshaped the healthcare industry, providing solutions to challenges in disease prevention, monitoring, and control. With the rise of Industry 5.0 and 5G, the development of cost-effective sensors enables real-time health monitoring, significantly enhancing patient care. This paper investigates the application of Artificial Intelligence (AI) and Deep Learning